Evaluation of Superparamagnetic Fe3O4-Ag Decorated Nanoparticles: Cytotoxicity Studies in Human Fibroblasts (HFF-1) and Breast Cancer Cells (MCF-7) - Reyes-López, Simón Yobanny (2024)
This study investigates the cytotoxicity profile of superparamagnetic Fe3O4-Ag decorated nanoparticles against human fibroblasts (HFF-1) and breast cancer cells (MCF-7). The nanoparticles underwent comprehensive characterization employing scanning electron microscopy (SEM), X-ray diffraction (XRD) analysis, X-ray photoelectron spectroscopy (XPS), and magnetic assays including hysteresis curves and zero-field-cooled (ZFC) plots. The nanoparticles exhibited superparamagnetic behavior as evidenced by magnetic studies. Cytotoxicity assays demonstrated that both HFF-1 and MCF-7 cells maintained nearly 100% viability upon nanoparticle exposure, underscoring the outstanding biocompatibility of Fe3O4/Ag decorated nanoparticles and suggesting their potential utility in biomedical applications such as drug delivery and magnetic targeting. Furthermore, the study analyzed the cytotoxic effects of Fe3O4 and Fe3O4-Ag decorated nanoparticles to evaluate their biocompatibility for further therapeutic efficacy. Results showed that neither type of nanoparticle significantly reduced cell viability in HFF-1 fibroblasts, indicating non-cytotoxicity at the tested concentrations. Similarly, MCF-7 breast cancer cells did not exhibit a significant change in viability when exposed to different nanoparticle concentrations, highlighting the compatibility of these nanoparticles with both healthy and cancerous cells. Additionally, the production of reactive oxygen species (ROS) by cells exposed to the nanoparticles was examined to guarantee their biosafety for further therapeutic potential. Higher concentrations (50–100 μg/mL) of Fe3O4-Ag nanoparticles decreased ROS production in both HFF-1 and MCF-7 cells, while Fe3O4 nanoparticles were more effective in generating ROS. This differential response suggests that Fe3O4-Ag nanoparticles might modulate oxidative stress more effectively, thus beneficial for future anticancer strategies due to cancer cells’ susceptibility to ROS-induced damage. These findings contribute to understanding nanoparticle interactions with cellular oxidative mechanisms, which are crucial for developing safe and effective nanoparticle-based therapies. This investigation advances our understanding of nanostructured materials in biological settings and highlights their promising prospects in biomedicine.